The synchronous primary carcinomas of the rectum and prostate - Semin Ayhan; Arzu Ozdamar; Nalan Nese; Hasan Aydede (Wolters Kluwer Medknow Publications, 2011)
The diagnosis of synchronous prostatic and rectal carcinomas is uncommon. To make a correct diagnosis, biopsies of both sites are mandatory. Pathological slides should be compared and immunohistochemical staining should be taken into consideration. In this paper, an unexpected case of synchronous rectal and prostatic carcinomas arising in an 84-year-old male with hematemesis and pelvic pain is reported. These two tumoral components have a distinctive histological appearance. Immunohistochemical evaluation confirmed the diagnosis of these synchronous tumors. This case emphasizes that rectal and prostatic carcinomas can arise simultaneously. In this situation, providing clinicopathological correlation and deciding the necessity of intraoperative consultation in proper time are extremely important.